2018
DOI: 10.3390/atmos9070281
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Taklimakan Dust Events on Chinese Urban Air Quality in 2015

Abstract: Aerosols are an important factor affecting air quality. As the largest source of dust aerosol of East Asia, the Taklimakan Desert in Northwest China witnesses frequent dust storm events, which bring about significant impacts on the downstream air quality. However, the scope and timing of the impacts of Taklimakan dust events on Chinese urban air quality have not yet been fully investigated. In this paper, based on multi-source dust data including ground observations, satellite monitoring, and reanalysis produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 63 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…Dust aerosols have a significant impact on the radiative energy balance of the Earthatmosphere system by scattering and absorbing solar and infrared radiation [1][2][3][4], and can also indirectly affect the global climate system by affecting the optical properties of clouds [5][6][7]. Dust aerosols can reduce air quality and visibility [8][9][10], with serious implications for human health [11,12]. In addition to affecting local air quality, trace elements (such as Fe) and nutrients in dust aerosols also affect marine biogeochemical cycles through long-range transport and deposition, enhancing carbon uptake by the ocean [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Dust aerosols have a significant impact on the radiative energy balance of the Earthatmosphere system by scattering and absorbing solar and infrared radiation [1][2][3][4], and can also indirectly affect the global climate system by affecting the optical properties of clouds [5][6][7]. Dust aerosols can reduce air quality and visibility [8][9][10], with serious implications for human health [11,12]. In addition to affecting local air quality, trace elements (such as Fe) and nutrients in dust aerosols also affect marine biogeochemical cycles through long-range transport and deposition, enhancing carbon uptake by the ocean [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies in developed areas of China, such as the Yangtze River Delta, the Pearl River Delta, and the North China Plain, have been conducted on urban air quality based on long-term air pollution data combined with a variety of experimental and modeling methods 17 , 18 . However, in Xinjiang, a relatively underdeveloped region in northwest China, urban air research has focused on the characteristics, meteorological effects and sources of air pollution in heavily industrialized cities on the northern slopes of the Tianshan Mountains 19 ; The impact of the 2015 Taklamakan dust event on the air quality of urban areas in China 20 ; Analysis of emission reduction measures and simulation study of PM 2.5 concentration in Xinjiang's main cotton production area, and study of spatial 21 and temporal characteristics of air pollution (PM 2.5 , PM 10 , SO 2 , NO 2, CO, and O 3 ) in surrounding areas caused by a large amount of wind-blown sand from the desert (Taklamakan Desert) 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the combination of satellite remote sensing and ground-based observation data provides a good analysis of dust storm events, including identifying dust source areas and propagation trajectories [17][18][19][20][21][22][23][24][25][26]. For example, Guo et al [24] utilized the aerosol optical depth (AOD) data from MODIS aboard Satellite Aqua, along with the altitude-resolved aerosol types from CALIOP and surface PM 10 measurements, to investigate the dust activities in the springtime of northern China.…”
Section: Introductionmentioning
confidence: 99%